STRATEGI PENINGKATAN PRODUKSI PADI MELALUI UPSUS PAJALE DAN KONTRIBUSINYA TERHADAP PENINGKATAN EKONOMI DI KABUPATEN ACEH BESAR - Teuku Mizan Maulana; Romano Romano; Mustafa Usman (Jurnal Bisnis Tani, 2017)
Indonesia is one of agrarian countries in the world that rely on the agricultural sector in support of itseconomy. Indonesia had been a self-sufficient country in 1984 and now the government of President Joko Widodo with his Work Cabinet had established UPSUS Pajale program to achieve back the selfsufficiencythat ever lost. This research was conducted in order to analyze UPSUS Pajale strategy in increasing rice production in Big Aceh District and contribution of increasing rice production to economic improvement in Big Aceh District. The results showed that UPSUS Pajale in Big Aceh District did not increase rice production, even decreased production to 230,985 tons in 2015 and 199,248 tons in 2016 compared to before the implementation of UPSUS Pajale 264,190 tons in 2014 and 243,734 tons in 2013. UPSUS Pajale strategy that needs to be implemented in increasing rice production in Big Aceh District is SO (Strength-Opportunity). The implementation of the UPSUS Pajale program in Big Aceh District did not result an increase in the contribution of paddy production to the PDRB and agricultural sector PDRB, and even a decline in rice contribution during the implementation of UPSUS PajaleKeywords: UPSUS Pajale, rice production, regional economic growth